Addressing the challenge of first metatarsal head ulcers: preliminary results of a minimally invasive base osteotomy approach - Lopez, Valeria; Gonzalez, Emanuel; Gaitan, Laura; Slullitel, Gaston; Varela, Maria Jose; Alvarez, Gonzalo; Randolino, Juan Pablo (Journal of the Foot & Ankle, 2026)
Objective: This study reports preliminary results of a minimally invasive first metatarsal base osteotomy for chronic plantar diabetic foot ulcers (DFUs). Methods: Five consecutive patients with neuropathic DFUs under the first metatarsal head, unresponsive to at least six weeks of conservative treatment, were enrolled. Patients with severe ischemia, osteomyelitis, or significant soft tissue loss were excluded. All underwent a dorsomedial percutaneous incomplete wedge osteotomy of the first metatarsal base, performed by a single surgeon. Ulcer care and postoperative follow-up were conducted according to standardized protocols. Results: All ulcers healed within weeks, with no cases of radiographic nonunion, transfer lesions, or recurrence at a mean follow-up of 12 months. One superficial infection resolved with oral antibiotics. Conclusion: These preliminary findings suggest that minimally invasive first metatarsal base osteotomy may be a feasible surgical option for selected patients with chronic plantar DFUs refractory to conservative care. Larger, controlled studies are warranted to validate its safety, effectiveness, and long-term outcomes. Level of evidence IV; Case series.